Quel(s) besoin(s) d'accomplissement pour quelles carrières ? Une exploration dans le contexte tunisien pour mieux comprendre l'attrait pour la carrière entrepreneuriale - Ilia Taktak Kallel (Nantes Université, 2012)
The need of achievement is recognized to be one of the most powerful engines of the human activity. It is widely allowed, after the works of Mc Clelland (1961) that the entrepreneurs are particularly lived by this need. Is the need of achievement the privilege of any or does it lead all the individuals? Is its expression the same from a culture to another one? If the work offers the opportunity to revisit these various questions, the ambition is to understand which psychological needs and values are congruents with which career preferences in the Tunisian context and - finally to encircle some of the engines which can explain the interest for the entrepreneurship career. In that purpose, a survey by questionnaire was led with 213 students of a business school in Tunisia. The results reveal in particular that the need of fulfillment is especially congruent with situations of indecision in terms of career preferences, while the choice of the entrepreneurship career significantly keeps pace with the search for a certain quality of life, what brought to us to advance the idea of "feminization" of the values of individuals attracted to new business start-up, even if this last one remains a widely male career.